The Contribution of Labors to the Income of Pig Farming Business in the Tropical Coastal Papua Barat - Jhonly Woran; Mulyadi Mulyadi; Lusia Keworip; Stepanus Pakage; Desni Saragih; Meky Sagrim; Lily Orisu; Deny Anjelus Iyai (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
The purpose of this study was to determine the type of work and division of labor in the household-scale pig farm business and how much income was earned and generated by each male, adult female and child labor as a case study in the Manokwari coastal agroecological area Papua Barat. The method used is descriptive research method with survey techniques through interviews and field observations. The sample of farmers chosen purposively was 35 households out of 50 pig breeder. Farmers selected as samples are those who have been running pigs for more than 1 year. The parameters measured are labor involvement and contribution of economic beneficiaries. Data were analyzed using descriptive statistics and inferential statistics, namely analysis of variance with further testing Scheffe using SPSS v.16.0. The results showed that the types of work carried out by domestic workers included processing and providing [A4] food, medicine and sanitation, selling live cattle on the market and selling carcasses. Female breeders have almost the same level of participation as men. In terms of working hours, women give higher time (521 hours/month) in 6 pig raising activities. Female workers contribute higher incomes than male workers.